The Semantics of Sharpness and the Prohibition of the Pungent: Garlic, Sanskrit śigru(ka)-, and Old Persian *θigra(ka)- - Spiers, Carmen S. (Indo-Iranian journal, 2022)
This study proposes a new understanding of the semantics behind Sanskrit śigru-, which Lubotsky (2002) suggested is a loanword from Scythian related to Old Persian *θigra(ka)- and Modern Persian sīr “garlic.” Although śigru- has been assumed to refer to Moringa oleifera Lam. “drumstick tree,” Meulenbeld (2009=2018) has shown that in Āyurvedic literature it is not exclusively used to denote moringa, but must have referred to various pungent, pro-pitta plants. Lubotsky proposed that what links śigru- (as moringa) to Iranian words for garlic is the idea of a sharp shape. However, given Meulenbeld’s conclusions, enhanced by the survey of śigru- in non-Āyurvedic literature undertaken here, the author proposes that the connection is sharp taste rather than shape. The pungent connection is supported by the fact that Dharma texts forbid eating śigru- along with garlic and onions, as well as by semantic developments of the Sanskrit root tij-. Finally, the survey allows for some cultural explanations of the traditional garlic-and-onion prohibition.